The relationship between the insecticide dichloro-diphenyl-trichloroethane and chloroquine in Plasmodium falciparum resistance - Makowa, Hazel Beverly (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.